DEVELOPMENT OF EXPORT SERVICES RENDERED BY BELARUS TRANSPORT - A. A. Kossovsky; I. D. Antioushenia (Наука и техника)
The paper determines competitive advantages of the Republic of Belarus in the world market of transport services. Belarus is the most important communication corridor between European countries that creates the required conditions for export development of transport services.The authors reveal deterrents concerning an increase of service export volume, prepare well-reasoned conclusion that there are  significant reserves for higher efficiency of transport industry activity. In order to use these reserves it is necessary to direct efforts for searching rational ways to solve the problems including application of  logistics methods.